2018
DOI: 10.3390/md16100343
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel Aspochalasins from the Gut Fungus Aspergillus sp. Z4

Abstract: Two novel aspochalasins, tricochalasin A (1) and aspochalasin A2 (2), along with three known compounds (3–5) have been isolated from the different culture broth of Aspergillus sp., which was found in the gut of a marine isopod Ligia oceanica. Compound 1 contains a rare 5/6/6 tricyclic ring fused with the aspochalasin skeleton. The structures were determined on the basis of electrospray ionisation mass spectroscopy (ESIMS), nuclear magnetic resonance (NMR) spectral data, and the absolute configurations were fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Compounds 84-91 were identified and characterized as having a spiro-heterocyclic γ-lactam skeleton and they were isolated from a culture broth of the marine fish-associated endophytic fungi A. fumigatus [50]. Compounds 92-96 were characterized as four aspochalasin analogs and they were obtained from the intestines of the marine isopod Ligia oceanica, collected along the coast of Dinghai in Zhoushan, Zhejiang Province, China [51][52][53]. Aspochalasins are a small group of cytochalasans structurally featuring a macrocyclic ring system and perhydroisoindol-1-one unit with an isobutyl side chain.…”
Section: Diketopiperazine Alkaloidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compounds 84-91 were identified and characterized as having a spiro-heterocyclic γ-lactam skeleton and they were isolated from a culture broth of the marine fish-associated endophytic fungi A. fumigatus [50]. Compounds 92-96 were characterized as four aspochalasin analogs and they were obtained from the intestines of the marine isopod Ligia oceanica, collected along the coast of Dinghai in Zhoushan, Zhejiang Province, China [51][52][53]. Aspochalasins are a small group of cytochalasans structurally featuring a macrocyclic ring system and perhydroisoindol-1-one unit with an isobutyl side chain.…”
Section: Diketopiperazine Alkaloidsmentioning
confidence: 99%
“…Aspochalasins are a small group of cytochalasans structurally featuring a macrocyclic ring system and perhydroisoindol-1-one unit with an isobutyl side chain. Among them, the structure of compound 92 includes a unique 5/6/6 tricyclic ring fused with the skeleton of aspochalasin [51]. Compounds 94 and 95 represent the first thiomethyl-substituted aspochalasin analogs [52].…”
Section: Diketopiperazine Alkaloidsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was evaluated for cytotoxic effect against prostate cancer cell line (PC3), showing strong activity with IC 50 value of 11.14 mM. 32 Cordyol C-3-O-a-D-ribofuranoside (61), 7-ethyldiorcinol (62), 3-hydroxydiorcinol (63), glyceryl diorcinolic acid (64), cordyol C (65), and aspergilol E (66), are six diphenyl ethers, which were puried from the marine-derived Aspergillus sydowii (ethyl acetate extract). These diphenyl derivatives were assayed for their cytotoxic effects against different cancer cell lines, including U937, 4T1, HT-29, PC3, HL-60, K562, A549 and NCI-H460, exhibiting selective cytotoxicity with IC 50 values varying between 3.36 AE 0.68 and 23.03 AE 1.345 against multiple cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…A novel nucleoside, elucidated as 3′- O - (α-D-glucosyl) inosine, had been isolated from Ligia exotica but its bioactivity was not identified 24 . Similarly, two novel aspochalasins have been isolated from the gut fungus which was found in marine isopod Ligia oceanica 25 . Yue et al 26 not only demonstrated the pharmaceutical value of L. exotica for pain-relief in Chinese folk medicine, but also suggested that sea slaters may represent a promising source for discovery of novel analgesic and anti-inflammatory compounds in near future.…”
Section: Introductionmentioning
confidence: 99%